2018
DOI: 10.1021/acs.inorgchem.7b02658
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Electrocatalytic Activity of Ammonium Nickel Phosphate, [NH4]NiPO4·6H2O, and β-Nickel Pyrophosphate, β-Ni2P2O7: Catalysts for Electrocatalytic Decomposition of Urea

Abstract: Electrocatalytic decomposition of urea for the production of hydrogen, H for clean energy applications, such as in fuel cells, has several potential advantages such as reducing carbon emissions in the energy sector and environmental applications to remove urea from animal and human waste facilities. The study and development of new catalyst materials containing nickel metal, the active site for urea decomposition, is a critical aspect of research in inorganic and materials chemistry. We report the synthesis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…At the same time, the peak current response heightens conspicuously in the anode and weakens in the cathode when 1.0 mM urea was injected (curve a). It has been reported that a cost-effective nickel-based catalyst can convert urea into non-poisonous and harmless nitrogen gas products under alkaline conditions by electro-oxidation, 25 and the electrocatalytic process of this material towards urea may occur as follows: 8,17,20,26 Ni…”
Section: Electrochemical Behaviors Towards Ureamentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the peak current response heightens conspicuously in the anode and weakens in the cathode when 1.0 mM urea was injected (curve a). It has been reported that a cost-effective nickel-based catalyst can convert urea into non-poisonous and harmless nitrogen gas products under alkaline conditions by electro-oxidation, 25 and the electrocatalytic process of this material towards urea may occur as follows: 8,17,20,26 Ni…”
Section: Electrochemical Behaviors Towards Ureamentioning
confidence: 99%
“…The DPV measurements manifest that the electrooxidation course keeping accordance with the switch from Ni(II) to Ni(III) is affected by the increasing concentration of urea and it is simultaneously electro-oxidized to nitrogen gas in this process. 25 Linear sweep voltammetry response of urea. Linear sweep voltammetry (LSV), similar to cyclic voltammetry (CV), is also a kind of common electrochemical test means, which is oen used for quantitative determination of adsorbent substances.…”
Section: Evaluation Of Electrochemical Performancesmentioning
confidence: 99%
“…The study and development of new catalyst materials containing nickel metal, the active site for urea decomposition, is a critical aspect of research in inorganic and materials chemistry. The [NH 4 ]NiPO 4 ·6H 2 O calcined at 300°C with an amorphous crystal structure has the greatest reported electroactive surface area (ESA) of 142 cm 2 /mg and an onset potential of 0.33 V (SCE) and was stable over a 24‐hour test period …”
Section: Introductionmentioning
confidence: 99%
“…The α → β transition occurs at 573 K when M = Co and at 838 K when M = Ni . In the β‐M 2 P 2 O 7 (M = Co, Ni) monoclinic structure, with Z = 2 and standard space group C 1 2/m 1, all M(II) ions are in octahedral sites and all P(V) are in tetrahedral sites.…”
Section: Introductionmentioning
confidence: 99%
“…Because Ni 2+ oxidizes to Ni 3+ more easily before the reaction starts, more electroactive sites will be obtained [20][21][22]. Compared with NiO, which is a typical electrocatalytic material for UOR, the energy of Ni2P is significantly lower, because of the lower energy of the Ni-P bond compared to that of Ni-O [23][24][25]. Nevertheless, the weak stability hinders its wide application.…”
Section: Introductionmentioning
confidence: 99%